2007 IEEE Particle Accelerator Conference (PAC) 2007
DOI: 10.1109/pac.2007.4440323
|View full text |Cite
|
Sign up to set email alerts
|

Generation of subpicosecond x-ray pulses in storage rings

Abstract: Supicosecond x-ray pulses are routinely produced at ALS, BESSY and SLS with "slicing" technique and used in pump-probe experiments with controlled delay between laser pump pulses and x-ray probe pulses. New development aiming for a production of a subpicosecond x-ray pulses using rf orbit deflection technique is under way at APS. Both techniques will be reviewed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is found that using strong modulations [normalized amplitude jKj & 4, K is defined by Eq. (2.2) below], the bunch length can be significantly reduced (see [8][9][10][11][12] for other methods for short bunches). However, the linearized model becomes invalid for strong modulations, in which case the nonlinearity arisen from the sine function dominates the dynamics of the SSMB system.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that using strong modulations [normalized amplitude jKj & 4, K is defined by Eq. (2.2) below], the bunch length can be significantly reduced (see [8][9][10][11][12] for other methods for short bunches). However, the linearized model becomes invalid for strong modulations, in which case the nonlinearity arisen from the sine function dominates the dynamics of the SSMB system.…”
Section: Introductionmentioning
confidence: 99%